Forests and people: safeguarding the natural heritage in Brazilian Amazon - García Fernandez, C.; Shanley, P. (2004)
In the Brazilian Amazon, deforestation and fragmentation of tropical forests are estimated to affect one third of the region. Despite the attention given to tropical forest loss, rare mention is made of the direct loss of food, medicine and shelter to the local inhabitants. As the arc of deforestation catalyzed by logging spreads across Amazonia, data illustrating how people and valuable species respond under different conditions - and the consequences - become ever more relevant across a broad geographic range. The Forests and People project of CIFOR documents the changes that deforestation is bringing to the ecology, use and management of non-timber forest resources. The goal of the project is to generate relevant scientific and cultural information about the local value of forests, targeting a broad public from urban citizens to decison makers and health, agricultural and forestry training programs. Forest communities are the primary audience for research results since they have scant information on which to make critical decisions regarding the sale and use of forest resources.